7-Dehydrocholesterol attenuates osteoarthritis by synergistically inhibiting oxidative stress, inflammation, and ferroptosis in macrophages - Zhang, Wenchao; Hua, Mengru; Zhao, Xinyu; Sun, Guangxin; Pan, Yuheng; Miao, Le; Chen, Xuzhuo; Zhang, Shanyong (Frontiers in Pharmacology, 2026)
ObjectiveOsteoarthritis (OA) is a prevalent degenerative disorder affecting joints, characterized by progressive cartilage deterioration, inflammation of the synovium, and structural damage to subchondral bone. Inflammation mediated by synovial macrophages is a key driver of OA progression. Emerging evidence indicates that macrophage ferroptosis in inflamed synovium plays a pivotal role in disease advancement. 7-Dehydrocholesterol (7-DHC), an endogenous sterol with potent antioxidant properties due to its conjugated diene structure, effectively inhibits lipid peroxidation and ferroptosis. This study aimed to investigate whether 7-DHC delays OA progression by suppressing oxidative stress, inflammatory responses, and ferroptosis.MethodsTo explore the mechanisms underlying inflammation in vitro, RAW 264.7 macrophages were stimulated using lipopolysaccharide (LPS). The effects of 7-DHC treatment were subsequently evaluated by measuring reactive oxygen species (ROS) production, levels of inflammatory cytokines, and expression of ferroptosis-related proteins including GPX4 and ACSL4. Reverse transcription quantitative polymerase chain reaction (RT-qPCR), immunofluorescence (IF), and Western blotting (WB) techniques were utilized to clarify the associated molecular pathways. Additionally, to verify the in vivo efficacy, an OA mouse model was established by administering complete Freund’s adjuvant (CFA) into the joint cavity, enabling assessment of inflammatory changes in synovial tissues and bone structural modifications following 7-DHC intervention.ResultsThe findings from RAW 264.7 macrophages stimulated with LPS indicated significant inhibition of ROS accumulation, downregulation of pro-inflammatory cytokines such as TNF-α and IL-1β, and normalization of ferroptosis-associated protein expression patterns after 7-DHC application. Additionally, 7-DHC markedly suppressed phosphorylation of MAPK/NF-κB pathway proteins while enhancing expression of Nrf2/HO-1 pathway proteins. In vivo experiments confirmed that 7-DHC significantly reduced inducible nitric oxide synthase (iNOS) expression in inflamed synovial tissue, promoted expression of GPX4, a key lipid peroxidation inhibitor, and improved the oxidative stress environment of synovial tissues. Consequently, knee joint inflammation and bone destruction were markedly alleviated in mice.Conclusion7-DHC exerts anti-inflammatory and antioxidant effects by inhibiting the ROS/MAPK/NF-κB pathway and activating the Nrf2/HO-1 pathway. This reduces oxidative damage, inflammation, and ferroptosis in macrophages, thereby delaying OA progression. As a promising therapeutic strategy, 7-DHC may provide new research directions and clinical translational opportunities for OA treatment.